Centro de investigación de la flora y fauna silvestre en el Parque Zoológico y Jardín Botánico Nacional Simón Bolivar - Cordero-Arias, Gerald Martín (Instituto Tecnológico de Costa Rica., 2019)
Since its establishment in 1916, the Zoo and National Botanical Garden Simón Bolivar has been an institution committed to the conservation, research and education of the general population. This institution, located in the city of San José (Barrio Amón), is home to a wide variety of species of flora and fauna, which brings millions of visitors from all over the country and abroad during its more than 100 years of history. Despite the history and relevance it has had within the Costarican society, the Simón Bolívar Park is facing a serious popularity crisis in the eyes of different social groups that constantly ask for the absolute closure of its facilities. The lack of maintenance, poor advertising management and stagnation in an old model of zoo from the early 20th century are some of the causes of the state of deterioration of the park; for this reason, there are many intervention plans in favor of its rescue. The Wild Flora and Fauna Investigation Center Project seeks to break the paradigm of zoo that is associated with the Simón Bolívar Park, providing the necessary infrastructure to develop alternative activities that adapt to the values and customs of the Costarican society, promoting the conservation of our natural heritage through scientific research, taking into consideration criteria of sustainable architecture that takes advantage of resources from its location and taking part in the National Decarbonization Plan 2018-2050 through architecture.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Centros de investigación; Parques zoológicos; Jardines botánicos; Arquitectura